THE DEVELOPMENT INTERACTIVE LEARNING MEDIA ON LINEAR PROGRAM WITH MACROMEDIA FLASH 8 HOTS EXERCISES FOR STUDENT OF SMA/MA IN CLASS XI - Putri Wulandari; Suparman Suparman (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
This study aims to develop learning media on a linear program with Macromedia Flash 8 HOTS exercises for SMA/MA students in class XI. This research is included in the research and development using the development model of ADDIE consisting of five-phase, namely analysis, design, development, implementation, and evaluation. The research subject is media experts, material experts, and student response of State Senior High School (SMA Negeri) 1 Kasihan and SMA Negeri 1 Sanden Kabupaten Bantul. Data collection techniques in the form of questionnaires, observation, interviews, and exercises were done before developing the product. The research instrument used is observation sheet, interview sheet, and questioners to assess the interactive learning media that has been developed. The data analysis technique uses qualitative analysis that is converted into a Likert scale cumulative value. The results of the expert assessment of the media obtained an average score 4,58 very good category, by the expert assessment of the materials obtained an average score of 4,50 very good category, the student responses to the technical quality assessed in the small-scale trials obtained an average of 4,17 good category, and the student responses to the technical quality assessed in the classroom usage test scored an average of 4,44 very good category. Based on the average, the learning media of mathematics developed is a media of mathematics learning.